2020
DOI: 10.1007/s12028-020-01120-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Burden of Seizures and Highly Epileptiform Patterns in Critical Care with a Novel Machine Learning Method

Abstract: Introduction Current electroencephalography (EEG) practice relies on interpretation by expert neurologists, which introduces diagnostic and therapeutic delays that can impact patients’ clinical outcomes. As EEG practice expands, these experts are becoming increasingly limited resources. A highly sensitive and specific automated seizure detection system would streamline practice and expedite appropriate management for patients with possible nonconvulsive seizures. We aimed to test the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…They found that epileptologists, without automated data annotation, had a lower sensitivity (61%) but better false‐alarm rate (0.002/h) compared to the automated seizure‐detection algorithm (with no epileptologist involvement) that achieved a sensitivity of 90% and a false‐alarm rate of 0.087/h. Finally, Karmousi et al 42 evaluated a machine learning method to automatically estimate “seizure burden,” defined as the number of 10 s epochs with seizure activity in any 5 min period, with thresholds for low, medium, and high seizure burden (seizure activity in 10%, 50%, and 90% of epochs); detection of high seizure burden was used to generate a “status epilepticus” alert. EEG data were collected using the Ceribell in patients in the ICU.…”
Section: Results: 20 Years Of Progress In the Application Of New Noni...mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that epileptologists, without automated data annotation, had a lower sensitivity (61%) but better false‐alarm rate (0.002/h) compared to the automated seizure‐detection algorithm (with no epileptologist involvement) that achieved a sensitivity of 90% and a false‐alarm rate of 0.087/h. Finally, Karmousi et al 42 evaluated a machine learning method to automatically estimate “seizure burden,” defined as the number of 10 s epochs with seizure activity in any 5 min period, with thresholds for low, medium, and high seizure burden (seizure activity in 10%, 50%, and 90% of epochs); detection of high seizure burden was used to generate a “status epilepticus” alert. EEG data were collected using the Ceribell in patients in the ICU.…”
Section: Results: 20 Years Of Progress In the Application Of New Noni...mentioning
confidence: 99%
“…Two of the studies presented some quality concerns. Frankel and colleagues 27 used a nonbalanced number of events for the evaluation of the diagnostic accuracy of manual seizure detection (31 epochs with ictal events and 83 nonictal), whereas Kamousi et al 42 pointed out that their cohort contained a relatively low number of patients with high seizure burden (9 of 353 EEG studies).…”
Section: Results: 20 Years Of Progress In the Application Of New Noni...mentioning
confidence: 99%
“…Additionally, emerging hardware and software solutions that allow for rapid-response EEG can reduce time to diagnosis and definitive therapy as well as length of hospital stay for inpatients with suspected seizures. 82 Technological advances can also support more efficient deployment of aEEG in the nonacute setting.…”
Section: Futurementioning
confidence: 99%
“…The future of tele-EEG is exciting in that spike and seizure detection algorithms can directly scale these diagnostic services 82 by reducing constraints imposed by personnel shortages and can also help us study the clinical questions that may validate and grow the current models of utilization. 47 While subtle seizures can go undetected by these software, the algorithms have become astonishingly accurate relative to board-certified clinical neurophysiologists.…”
Section: Futurementioning
confidence: 99%
“…A retrospective cohort study reported high performance of clarity in 353 adult patients in the emergency departments and critical care units across six academic and community hospitals who underwent evaluation for altered mental status and NCSE using the RRLM-EEG device [ 30 ]. When compared with neurologists, authors reported high sensitivity (100%) and specificity (93%) when evaluating EEG with > 90% seizure burden in status epilepticus.…”
Section: Artificial Intelligencementioning
confidence: 99%